Strengthening Independent Learning through Humanistic and Adaptive Learning to Improve the Quality of Physical Education for Special Needs Students in Dompu Regency - Amal Fauqi; Linda Susila; Risky Aris Munandar; Mohammad Zaim Zen (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to analyze the strengthening of Freedom to Learn through humanistic and adaptive learning in improving the quality of education for students in Special Needs Schools (SLB) in Dompu Regency. The study used a literature review method by reviewing various regulations, policies, books, scientific articles, and related research results. The results of the study indicate that Freedom to Learn aligns with the principles of special education that focus on the needs, characteristics, and potential of students. Humanistic learning encourages the creation of a learning environment that respects the uniqueness and dignity of students, while adaptive learning allows for the adjustment of strategies, media, and assessments to suit individual needs. However, its implementation still faces obstacles such as limited teacher competency, a lack of adaptive media, inadequate facilities and infrastructure, and suboptimal support from the educational ecosystem. The research findings confirm that the main challenge for special needs education today is not only access to services, but also the ability to deliver meaningful, inclusive, and equitable learning. Therefore, strengthening Freedom to Learn in SLB requires responsive policies, improved teacher competency, the use of inclusive technology, and collaboration between schools, families, communities, and the government to improve the quality of education services and optimize student potential in a sustainable manner.